New treatment options for patients with brain metastases from ovarian cancer - A. G. Kedrova; S. E. Krasilnikov; A. G. Vinokurov; A. I. Berishvili; T. A. Greyan; O. P. Krashenkov; E. S. Polovnikov (Опухоли женской репродуктивной системы, 2021)
Brain metastases from ovarian cancer are quite rare: they affect no more than 0.5–3.0 % of patients according to the literature. However, the incidence of brain metastasis is increasing, which is attributed to longer survival of ovarian cancer patients and more accurate diagnosis. It is not possible to predict metastasis to the central nervous system, because reliable prognostic biomarkers have not been identified so far, although there have been some achievements in the treatment of such patients. Novel pathological and molecular tumor markers allow doctors to plan individual treatment for each patient and ensure good outcome. Many authors recommend combination treatment that includes surgical resection of the cerebral lesion followed by local radiotherapy alone or in combination with pharmacotherapy. The majority of these patients had high-grade serous ovarian carcinoma (HGSOC) and initially responded to chemotherapy with platinum and taxanes, while brain metastases were detected 2 to 4 years after treatment initiation. Mutations in the BRCA1 and BRCA2 genes, as well as expression of androgen receptors in the primary tumor, may be the risk factors for metastases to the central nervous system and, therefore, should determine further treatment strategy. In this article, we analyzed 3 cases of ovarian cancer with brain metastases.